Episode-specific drinking-to-cope motivation, daily mood, and fatigue-related symptoms among college students. - Armeli, Stephen; O'Hara, Ross E; Ehrenberg, Ethan; Sullivan, Tami P; Tennen, Howard (Journal of studies on alcohol and drugs, 2014)
The goal of the present study was to examine whether within-person, episode-specific changes in drinking-to-cope (DTC) motivation from the previous evening were associated with concurrent daily mood and fatigue-related symptoms among college student drinkers (N = 1,421; 54% female).
Keywords: Adaptation, Psychological; Adolescent; Affect; Alcohol Drinking; Fatigue; Female; Humans; Male; Medical Records; Motivation; Students; Universities; Young Adult